Endoscopic Ultrasound-guided Transesophageal Biopsy of Parathyroid Adenoma - Balekuduru, Avinash Bhat; Venkatesh Rao, P. S.; Subbaraj, Satyaprakash Bonthala (Journal of Digestive Endoscopy, 2017)
Parathyroid adenoma (PTA) causing hyperparathyroidism and hypercalcemia leading to pancreatitis is reported. Endoscopic ultrasound (EUS) can help in the localization of PTA. We report a case of EUS-guided fine-needle aspiration biopsy-proven PTA which is not reported in literature to our knowledge.
Keywords: Endoscopic ultrasound; pancreatitis; parathyroid adenoma